Clinicopathological Spectrum of Oncocytic Cell Lesions in the Thyroid - Priya Pai; Swati Sharma; Suresh Pillai (Online Journal of Health & Allied Sciences)
Background: Oncocytic cells are thyroid follicular derived cells, associated with non-neoplastic and neoplastic thyroid lesions. Aim: The aim of the study is to discuss the spectrum of Oncocytic cell lesions with respect to their demographic, clinical, cytological and histopathological features. Materials and Methods: This is a 2-year retrospective study in which thyroidectomy specimens with diagnosis of Oncocytic cell lesions were analysed. Patient data was obtained from the Medical Records Department. Fine needle aspiration (FNA) and histopathology slides were retrieved from pathology archives. Results: Amongst 360 thyroid cases, 16 cases showed Oncocytic cell lesions. Of these 16 cases, 3 cases were Oncocytic cell nodules, 10 were Oncocytic adenomas, and 3 were Oncocytic carcinomas. In this study, ultrasound and FNA were not effective in differentiating benign and malignant Oncocytic cell lesions. Age range was 33-74 years, and male to female ratio was 1: 4.3. On FNA, cases ranged from Bethesda II to Bethesda V. On histology, Oncocytic cell lesions showed various patterns-follicular, trabecular, nested, solid and papillary. Association with lymphocytic thyroiditis and papillary carcinoma was observed. Follow up data was available for 12 cases. Conclusion: Oncocytes are found in non-neoplastic as well as in neoplastic conditions in the thyroid. While the clinical significance of oncocytic cells is still not well established in literature, identification of Oncocytic cell carcinomas is necessary, as these are aggressive neoplasms.